Analysis of gamma-glutamyltransferase in acute promyelocytic leukemia patients undergoing arsenic trioxide treatment. Issue 1 (1st January 2021) - Sui, Meijuan; Wei, Hong; Zhang, Qian; Xiu, Ruolin; Shen, Xiaohan; Zhang, Zhuo; Zhou, Jin
ABSTRACT: Objectives: The remarkable effect of arsenic trioxide (ATO) was verified, but elevated gamma-glutamyltransferase (GGT), aminotransferases (ALT and AST) are generally observed in acute promyelocytic leukemia (APL) patients undergoing ATO treatment. However, utilization of hepatoprotective agents or discontinuation of ATO may inhibit ATO efficacy. In order to maintain ATO effect from hepatoprotective agents' influence so we investigate relationships between single elevation in GGT and hepatocellular injury in this study. Methods: Correlation of GGT variation and leukocyte counts were analyzed in all 81 APL patients, correlations among liver enzymes (ALT, AST and GGT) were also analyzed in patients without prophylactic hepatoprotective agents. In following study, we take the clinical observation of changes in aminotransferases in patients with single elevation in GGT without hepatoprotective agents. Results: The average elevated GGT in the WBC abnormal group was more than the normal group (53.86U/L vs. 31.03U/L, P  = 0.008), a positive Pearson's correlation of GGT variation and changed leukocyte counts in patients without prophylactic hepatoprotective agents. There are no significant correlation between aminotransferases (ALT and AST) and GGT but correlation between ALT and AST was statistically significant ( R  = 0.649, P  = 0.000). For APL patients with single elevation in GGT, ALT and AST levels were normal throughout the ATO treatment without hepatoprotective agents. Conclusion: Single elevation in GGT without elevated aminotransferases can't be identified as hepatotoxicity, and the elevated levels of GGT are associated with increasing leukocyte counts. Continue single-agent ATO without prophylactic hepatoprotective agents is recommended in APL patients with single elevation in GGT, in order to maintain ATO effect.